Effect of Counteranions on the Conformational Equilibrium of 1-Butyl-3-methylimidazolium-Based Ionic Liquids. (11th December 2011) - Hatano, Naohiro; Takekiyo, Takahiro; Abe, Hiroshi; Yoshimura, Yukihiro
Abstract : We have investigated the nonspherical anion effect on the trans-trans (TT) and gauche-trans (GT) equilibrium in pure 1-butyl-3-methylimidazolium ([bmim] + )-based room temperature ionic liquids (RTILs) by the Raman spectroscopy. The intensity ratio of the [bmim] + cation in [bmim] + -based RTILs having nonspherical anions changes with nature of the anions. However, the enthalpy change of the [bmim] + cation is approximately −1.0 kJ/mol for all [bmim] + -based RTILs used in this study and is independent of the anionic species. The present results indicate that the conformational stability of the [bmim] + cation in [bmim] + -based RTILs including nonspherical anions is driven by the entropic contribution associated with the orientation and configuration of the [bmim] + cation with respect to the counteranion.